Consequences of Ultra-Violet Irradiation on the Mechanical Properties of Spider Silk - Wee Loong Lai; Kheng Lim Goh (Journal of Functional Biomaterials, 2015)
The outstanding combination of high tensile strength and extensibility of spider silk is believed to contribute to the material’s toughness. Thus, there is great interest in engineering silk for biomedical products such as suture or implants. Additionally, over the years, many studies have also sought to enhance the mechanical properties of spider silk for wider applicability, e.g., by irradiating the material using ultra-violet radiation. However, the limitations surrounding the use of ultra-violet radiation for enhancing the mechanical properties of spider silk are not well-understood. Here, we have analyzed the mechanical properties of spider silk at short ultra-violet irradiation duration. Specimens of spider silk were subjected to ultra-violet irradiation (254-nm wavelength, i.e. UVC) for 10, 20, and 30 min, respectively, followed by tensile test to rupture to determine the strength (maximum stress), extensibility (rupture strain), and toughness (strain energy density to rupture). Controls, i.e., specimens that did not received UVC, were also subjected to tensile test to rupture to determine the respective mechanical properties. One-way analysis of variance reveals that these properties decrease significantly (p < 0.05) with increasing irradiation duration. Among the three mechanical parameters, the strength of the spider silk degrades most rapidly; the extensibility of the spider silk degrades the slowest. Overall, these changes correspond to the observed surface modifications as well as the bond rupture between the peptide chains of the treated silk. Altogether, this simple but comprehensive study provides some key insights into the dependence of the mechanical properties on ultra-violet irradiation duration.